ANALISIS PENEGAKAN HUKUM ADMINISTRATIF, PERDATA, DAN PIDANA DI INDONESIA: TINJAUAN LITERATUR - Gunawan Widjaja (JOURNAL OF COMMUNITY DEDICATION, 2025)
Law enforcement is an important aspect in maintaining justice and order in Indonesia, particularly in the administrative, civil, and criminal law domains. This study aims to analyse the characteristics, challenges, and effectiveness of law enforcement in these three domains through a literature review approach from various sources such as books, journals, and legislation. The analysis shows that administrative law enforcement is preventive and efficient, although it still faces obstacles in terms of supervision and the integrity of officials. Civil law enforcement focuses on dispute resolution based on the principle of procedural justice, but is often hampered by lengthy processes and suboptimal enforcement of decisions. On the other hand, criminal law enforcement plays a role in maintaining social order through complex formal mechanisms and the protection of human rights, although there are still obstacles related to bureaucracy and the professionalism of officials. This study recommends regulatory reforms, capacity building for law enforcement officials, and the promotion of a culture of law among the public to support the effectiveness of law enforcement in Indonesia. Thus, it is hoped that the national legal system can function more fairly, transparently, and responsively to social dynamics.